2010
DOI: 10.1111/j.1558-5646.2009.00860.x
|View full text |Cite
|
Sign up to set email alerts
|

Biparental Inbreeding and Interremnant Mating in a Perennial Prairie Plant: Fitness Consequences for Progeny in Their First Eight Years

Abstract: Despite fundamental importance to population dynamics, mating system evolution, and conservation management, the fitness consequences of breeding patterns in natural settings are rarely directly and rigorously evaluated. We experimentally crossed Echinacea angustifolia, a widespread, perennial prairie plant undergoing radical changes in distribution and abundance due to habitat fragmentation. We quantified the effects of both biparental inbreeding and crossing between remnant populations on progeny survival an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
51
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 50 publications
(56 citation statements)
references
References 89 publications
3
51
0
Order By: Relevance
“…On the contrary, outcrossing may not always be beneficial, and outbreeding depression, resulting from effects of locally maladaptive alleles or gene combinations, can develop in successive generations (25). Little to no benefit of gene flow was shown in an experimentally subdivided population of the selfing species Triticum aestivum (26) and in matings among remnant prairie populations in the outcrossing species Echinacea angustifolia (27). In crosses between nonnative, diverged populations of the selfing plant, Avena barbata, Johansen-Morris and Latta (28) demonstrated that, although early-generation hybrids did not differ from the parental lineages in field and novel greenhouse conditions, late-generation hybrids had lower fitness.…”
Section: Resultsmentioning
confidence: 99%
“…On the contrary, outcrossing may not always be beneficial, and outbreeding depression, resulting from effects of locally maladaptive alleles or gene combinations, can develop in successive generations (25). Little to no benefit of gene flow was shown in an experimentally subdivided population of the selfing species Triticum aestivum (26) and in matings among remnant prairie populations in the outcrossing species Echinacea angustifolia (27). In crosses between nonnative, diverged populations of the selfing plant, Avena barbata, Johansen-Morris and Latta (28) demonstrated that, although early-generation hybrids did not differ from the parental lineages in field and novel greenhouse conditions, late-generation hybrids had lower fitness.…”
Section: Resultsmentioning
confidence: 99%
“…Lifetime fitness is the composite of survival over successive intervals and multiple components of reproduction, within reproductive episodes, as well as over possibly many episodes in a lifetime. Accordingly, fitness has a compound distribution that is far from Gaussian or any other standard sampling distribution (see for example, Figure 4 in Wagenius et al, 2010). Consequently, assumptions of standard methods, such as linear models, are routinely violated, necessitating caveats about statistical inferences and their implications (for example, Shaw, 1986) and sometimes multiple approaches to analysing the data at hand (Antonovics and Ellstrand, 1984).…”
Section: Aster Modeling To Support Study Of V a (W)mentioning
confidence: 99%
“…Inbred offspring would not have survived during either stage of the life cycle, such as at seed production, germination, seedling growth stages, and so on, whereas outcrossed progeny having relatively higher fitness have a higher probability of survival to the present time. Such a positive relationship between the genetic relatedness of parents and offspring fitness has also been observed in other plants (Hirao 2010;Seltmann et al 2009;Wagenius et al 2010). Our results were inferred from dominant markers, which have lower powers than microsatellites in sibship and parentage assignments (Gerber et al 2000).…”
Section: Discussionmentioning
confidence: 72%